2018
DOI: 10.1515/hf-2017-0113
|View full text |Cite
|
Sign up to set email alerts
|

Influence of timber moisture content on wave time-of-flight and longitudinal natural frequency in coniferous species for different instruments

Abstract: Non-destructive techniques (NDTs) are well suited for rapid estimation of timber properties, but NDT results are affected by several factors, the most important of which is the moisture content (MC) of wood. Much of the research in this context was limited to ultrasound measurement of a few wood species, mainly to Norway spruce. The present paper investigates the MC influence on the NDT results obtained by instruments based on ultrasound (two devices), impact stress waves (one device) and longitudinal vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…One possible explanation is that the hammer and accelerometer of the MTG instrument were too close to the edge of a board during the measurements on the smaller boards for optimum performance, although this cross-section is still within the permitted size range of the instrument (CEN 2009). Llana et al (2018a) found linear relationships between SWV obtained using five different devices on four pine species and MC measured on timber boards. The relationships were different above or below FSP, but the prediction of timber properties was not affected by MC.…”
Section: Influence Of Pre-sortingmentioning
confidence: 81%
“…One possible explanation is that the hammer and accelerometer of the MTG instrument were too close to the edge of a board during the measurements on the smaller boards for optimum performance, although this cross-section is still within the permitted size range of the instrument (CEN 2009). Llana et al (2018a) found linear relationships between SWV obtained using five different devices on four pine species and MC measured on timber boards. The relationships were different above or below FSP, but the prediction of timber properties was not affected by MC.…”
Section: Influence Of Pre-sortingmentioning
confidence: 81%
“…Hassan et al (2013) determined the dynamic modulus of elasticity as 11,000 N/mm 2 in small-clear Scots pine samples. In studies conducted on structural Scots pine timbers, Montero et al (2015) found 9,680 N/mm 2 at 12% moisture content, Arriaga et al (2012) found 10,900 N/mm 2 , and Llana et al (2018) found approximately 11,100 N/mm 2 . Güntekin et al (2013Güntekin et al ( , 2014 found the dynamic modulus of elasticity as 9,840 N/mm 2 using the vibration method for Turkish red pine structural timbers at 27.1% moisture content.…”
Section: Resultsmentioning
confidence: 97%
“…Most of the research works related to the MC influence on NDT results focused on acoustic and resonance techniques [28][29][30][31][32]. Most of them found a more substantial MC influence below than above the fiber saturation point (FSP) [33][34][35][36][37]. Fewer research works dealing with MC influence on NDT-punctual techniques (probing, drilling, and coring) were found [38][39][40].…”
Section: Introductionmentioning
confidence: 99%